EFIKASI TERAPI BONE MARROW MESENCHYMAL STEM CELL TERHADAP INFEKSI VIRUS HEPATITIS SYSTEMATIC REVIEW - Inggit Dana Ayu Wilujeng (2020)
The hepatitis B virus has infected 2 billion people and about 170 million people are infected with the hepatitis C virus in the world (Kemkes RI, 2014). Although treatment for hepatitis is available, there is hardly an effective drug to restore tissue in the liver that has been injured. Liver transplantation is the most effective treatment for end-stage liver fibrosis. It is effective to restore liver function and improve liver regeneration, but in in-vitro testing it appears that hepatocytes easily decrease to loss of viability. This review aims to find out the efficacy of bone marrow mesenchymal stem cell therapy against hepatitis virus infection. The design of this study is a literature study in the form of a systematic review with the PRISMA method and screening results obtained in 7 journals. Sampling was done based on inclusion and exclusion criteria. Results showed that BM-MSC can restore liver function, judging by the parameters of liver function values, indicating a better prognosis (MELD scores and others) Giving a high dose of 5 x 10^7 cells, did not give serious side effects or toxicity. More research on the efficacy of BM-MSC therapy against hepatitis virus infection still needs to be done.